2008
DOI: 10.1021/cm703354q
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Polymer Electrochromic Film Characterization Using Bipotentiostatic Control

Abstract: We report an analytical method which allows the systematic variation of color states of pairs of electrochromic conjugated conducting polymers with simultaneous spectroelectrochemical and colorimetric characterization of the resulting color summation. This method measures colors by transmitting light through two polymer films stacked together in electrolyte and under separate potentiostatic control. The polymers that were used in this work are poly(3,4-ethylenedioxythiophene) (PEDOT), poly(3,4-propylenedioxypy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
38
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 20 publications
0
38
0
Order By: Relevance
“…Conducting polymers have paid great attention of the scientific community due to their wide applications in various fields such as sensors [1], solar cells [2][3], electrochromic devices [4][5], electronic shielding [6], supercapacitors [7,8], among others. In this way, the morphology plays an important role in any application, once depending on the synthesis, counter ion, structural defects and crosslink defects presence, for instance, different morphologies can be obtained, and so on tunable electrochemical behavior [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Conducting polymers have paid great attention of the scientific community due to their wide applications in various fields such as sensors [1], solar cells [2][3], electrochromic devices [4][5], electronic shielding [6], supercapacitors [7,8], among others. In this way, the morphology plays an important role in any application, once depending on the synthesis, counter ion, structural defects and crosslink defects presence, for instance, different morphologies can be obtained, and so on tunable electrochemical behavior [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their ubiquitous nature, it is unsurprising that organic compounds constitute as ignificant group within the EC materials currently available. This includes the popularc lass of molecules known as the viologens, [2,12,13] as well as many other types of organic systems such as conducting polymers (e.g., PEDOT,p olyaniline, polythiophene), [6,[14][15][16] phenothiazine derivatives, [17,18] perylene and relatedd iimides, [19][20][21] and others. [22,23] We have recently reported that the one-electrone lectrochemicalr eduction of aromatic oxygen and sulfur para-substituted diesters induces intense colorc hanges, and have estimated their contrastr atios and chromatic efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge and based on an extensive search of the literature, the electrochromic lenses and sunglasses we report herein represent the best visible‐region electrochromic performance for dual‐polymer CP electrochromic systems to date. They also are, to our knowledge, the first practical implementation in working sunglasses, that is, they represent practical, functional, and applied polymers.…”
Section: Introductionmentioning
confidence: 99%